Fuzzy dark matter and the dark dimension - Luis A. Anchordoqui; Ignatios Antoniadis; Dieter Lüst (European Physical Journal C: Particles and Fields, 2024)
Abstract We propose a new dark matter contender within the context of the so-called “dark dimension”, an innovative 5-dimensional construct that has a compact space with characteristic length-scale in the micron range. The new dark matter candidate is the radion, a bulk scalar field whose quintessence-like potential drives an inflationary phase described by a 5-dimensional de Sitter (or approximate) solution of Einstein equations. We show that the radion could be ultralight and thereby serve as a fuzzy dark matter candidate. We advocate a simple cosmological production mechanism bringing into play unstable Kaluza–Klein graviton towers which are fueled by the decay of the inflaton.